Assessing food security indicators in Ba-Phalaborwa Local Communities, Mopani District, Limpopo Province, South Africa - Ralefatane, Moyahabo Elizabeth (My University, 2021)
This study investigated the food security indicators in the rural communities of Ba-Phalaborwa Local Municipality of the Limpopo Province. Quantitative data were gathered from five villages in the municipality using the probability proportionate to size. Data were collected from 185 households. The analytical tools that were used in this study include: Descriptive Statistics, Food Security Indicator Measures and the Logistic Regression Model. Food security is a multidimensional concept; thus it is difficult to measure it comprehensively. Hence, three food security indicators measures, namely; the Household Food Insecurity Access Scale (HFIAS), Household Dietary Diversity Score (HDDS) and Coping Strategies Index (CSI) were combined in this study to measure food security in the study. Each indicator measure was used independently. The Logit Regression Model was used to determine the factors affecting the status of household food security. Certain explanatory variables, namely; household size, marital status and receiving government grant, had a negative relationship with the dependent variable. On the other hand, other variables such as educational level, employment status, gender distance to the markets and health status of the household head were positively correlated with the household’s food security status. The study rejected the null hypothesis which stated that socioeconomic factors do not have influence on the households’ food security status in the Ba-Phalaborwa local municipality. Out of the 11 variables, only four variables were significant, with the household size at 10%, educational level at 5%, household monthly food expenditure at 1% and distance to the market at 10%, respectively. Therefore government should direct more focus should on the introduction of feeding schemes in order to reduce the burden on the poor and at the same time, make it easier for young children to attend school to improve their educational statuses. The households in the study area are not food secured because 65.4 % of households could not afford the food that they preferred and were depending on borrowing food from their relatives and creating debts.
Thesis (M. Sc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2021
Keywords: Food security indicators; Ba-Phalaborwa Local Communities; Mopani District; Limpopo Province; Human security; Agriculture -- Environmental aspects; Health status indicators -- South Africa; Food security